Time, Narrative Intimacy and the Child: Implications of the Transition from the Present to the Past Tense in the Translation into English of Children’s Texts - Lathey, Gillian (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2003)
AbstractThe British version of Jean de Brunhoff’s Histoire de Babar is a striking example of the transition from the present to the past tense in the translation of children’s texts into English. With reference to theories of narrative time, this paper invites speculation on the impact of such a tense shift on the present-tense qualities of the original, on the performance of a shared reading by child and adult and, finally, on the relevance of the young child’s developing understanding of the role of tense in narrative.